Bilateral Pagets Disease of Nipple - Begum, Mahbuba; Habib, Ahsan; Faisal, Shahrier; Chowdhury, MAM; Iqbal, KGM (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Pagets disease of nipple is a rare entity of malignant lesion of breast and bilateral Pagets disease is very uncommon. It presents as eczema like condition of the nipple areola which persists despite local treatment. As it is a superficial manifestation of underlying breast carcinoma high degree of suspicion is essential for proper recognition of this condition, so that early diagnostic work up can be initiated for differentiating it from other benign inflammatory skindisorder and for detecting an underlying breast carcinoma, thereby delay in proper treatment can be avoided in order to avoiding dismal consequences. Here we report a case of bilateral Pagets disease of nipple with invasive left breast carcinoma in a 40 year old lady diagnosed in Medical College for Women and Hospital, Uttara, Dhaka. J Bangladesh Coll Phys Surg 2016; 34(1): 33-36